Music as a social instrument: a brief historical and conceptual perspective - Bannan, Nicholas; Harvey, Alan R. (Frontiers in Cognition, 2025)
This article addresses the origins and purpose of communal music-making, including dance, and its role in human sociality. It accords special significance to the adapted nature of human vocalization, and the sensorimotor discrimination that allows the prediction and then generation of musically relevant, coordinated and simultaneous movements. Commencing with a historical survey of the development of ideas about the evolutionary importance of music in human social behavior, this mini-review then sets out to define and explore key issues involved in an evolutionary explanation. These include: acquisition and control of parameters required for vocal production (synchronization of pitch, timbre, duration and loudness); the exchange and transmission of pitched utterances in unison as well as in harmony; the roles of natural and sexual selection in shaping human musical abilities; the nature of cooperative behavior, and the consequences for social bonding of such interaction throughout life; transmission of such behaviors across generations, and the interaction between genes and culture that drives the evolution of complex social behavior in Homo sapiens. The article concludes with a brief review of current research that deals with contributory features of this field, especially in neuroscience which continues to provide important psychophysiological data that reinforces the long-held proposal that music has a key role in promoting cooperative, prosocial interactions leading to health and wellbeing over the human lifespan.